1995
DOI: 10.1128/jvi.69.12.7548-7558.1995
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evolution within the V3 loop domain of human immunodeficiency virus type 1 in association with disease progression

Abstract: Phylogenetic analysis was used to study in vivo genetic variation of the V3 region of human immunodeficiency virus type 1 in relation to disease progression in six infants with vertically acquired human immunodeficiency virus type 1 infection. Nucleotide sequences from each infant formed a monophyletic group with similar average branch lengths separating the sets of sequences. In contrast to the star-shaped phylogeny characteristic of interinfant viral evolution, the shape of the phylogeny formed by sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 53 publications
2
31
1
Order By: Relevance
“…Given the relatively low natural variation in the RT gene, this suggests that RT genes are relatively conserved evolutionarily. In the case of V3, ds/da ratios of about 1 were observed, but a positive Darwinian selection (ds/da Ͻ1) favoring diversity at the amino acid level has been described (16,29,43). This is consistent with the observation that for V3, some nonsynonymous substitutions are related to antibody enhancement, the biological phenotype of the virus, and resistance to neutralization.…”
Section: Fig 3-continuedsupporting
confidence: 80%
See 1 more Smart Citation
“…Given the relatively low natural variation in the RT gene, this suggests that RT genes are relatively conserved evolutionarily. In the case of V3, ds/da ratios of about 1 were observed, but a positive Darwinian selection (ds/da Ͻ1) favoring diversity at the amino acid level has been described (16,29,43). This is consistent with the observation that for V3, some nonsynonymous substitutions are related to antibody enhancement, the biological phenotype of the virus, and resistance to neutralization.…”
Section: Fig 3-continuedsupporting
confidence: 80%
“…A ds/da ratio of more than 1 generally means that the proteins have evolved under negative or purifying selection, because changes are deleterious and therefore eliminated. A ds/da ratio of less than 1 has been proposed to indicate forms of selection that lead to stable polymorphism, and such ratios have been observed in the variable region of gp120 of HIV-1 (16,29,43).…”
Section: Resultsmentioning
confidence: 99%
“…A study by Lukashov et al (25) comparing two sequences, one obtained during seroconversion and one determined 5 years later, from each of 44 individuals showed a positive correlation between the length of the immunocompetent period (CD4 counts Ͼ200) and the degree of nonsynonymous substitution, suggesting that slower progressors have stronger selective pressures for amino acid change. However, in five HIV-1-infected infants, Strunnikova et al (35) found an inverse correlation between average CD4 cell counts and the rate of sequence divergence. In a recent study of six patients, two moderate progressors and one slow progressor showed higher rates of nonsynonymous changes than one slow progressor and two rapid progressors (41).…”
mentioning
confidence: 97%
“…However, it should be pointed out that not even the REV model with a gamma distribution succeeded in accurately reconstructing the true branch lengths of the known phylogeny. The apparent substitution rates may be influenced by rate differences in different lineages or individuals (9,39) or by transmissions and other bottleneck effects (for instance, drug treatment). Preliminary data show that ancestral divergence and rapid substitution fluctuations also seem to influence the apparent rates and branch length estimates (to be published elsewhere).…”
Section: Discussionmentioning
confidence: 99%